PENGARUH MOTIVASI INTERNAL DAN EXTERNAL TERHADAP KINERJA KARYAWAN PT.TRUBAINDO COAL MINING DI KUTAI BARAT - Elfreda Aplonia Lau, Dedy Nor, LCA. Robin Jonathan (EKONOMIA, 2016)
The background of this research aspects of internal motivation and motivation eksternal. Data this study was obtained from the method of the results of responses of respondents (questionnaire), as well as other research relefan with the object under study, in this case the secondary data from the company PT.Trubaindo Coal Mining Kutai Barat analysis model used in this research is multiple linear regression analysis using SPSS 21.This study aims to determine the influence of motivation on employee performance and determine the dominant variable affecting employee performance. The sampling technique in this study using the technique of the census population is all employees of PT. Trubaindo Coal Mining Kutai Barat totaled 38 orang.Analisis used preformance of this research is multiple linear regression, hypothesis testing test F and test T.From the description of the phenomenon in the background, so in this study was formulated as follows:Is the internal motivation affects the performance of employees at PT Trubaindo Coal Mining Kutai BaratDoes External motivation affects the performance of employees at PT Trubaindo Coal Mining Kutai Barat.What was the motivation (internal and external) affect the performance of employees at PT Trubaindo Coal Mining Kutai BaratBased on the results of data analysis and discussion, it was concluded that:External motivation (X2) have a significant effect on employee performance (Y) PT.Trubaindo Coal Mining Kutai BaratInternal motivation (X1) effect on employee performance (Y) PT. Trubaindo Coal Mining Kutai BaratInternal motivation (X1) and external motivation (X2) have a significant effect on employee performance (Y) PT. Trubaindo Coal Mining Kutai Barat.By using a multiple linear regression analysis and hypothesis testing, it can be concluded that the hypothesis is accepted, that the internal motivation (X1), external motivation (X2), performance (Y) significantly affects the performance of employees of PT Trubaindo Coal Mining Kutai Barat